The impact of celebrity endorsement on consumer behaviour and brand perception: a study of Kpop culture's influence among the university students in Klang Valley - Wong, Teng Yi (2024)
This study examines the impact of K-POP celebrity endorsements on consumer behaviour and brand perception among university students in Malaysia’s Klang Valley region. The problem lies in understanding whether such endorsements influence consumer awareness, deliberation, and purchasing intention, and whether the image of K-POP celebrities aligns with the intended brand perception to foster long-term loyalty. A quantitative research method was employed, using a survey distributed to 55 university students aged 18 to 25, with 5 students participating in a pilot test. The findings reveal that K-POP endorsements significantly impact consumer decision-making processes, particularly in terms of brand awareness and consideration. Additionally, the study shows that a strong alignment between the celebrity’s image and brand values plays a critical role in enhancing brand loyalty and consumer engagement. Marketers are advised to strategically align celebrity endorsements with brand identity to maximize their influence on young consumers, as misalignment may lead to weaker brand loyalty. Further research is recommended to explore the long-term sustainability of such endorsements across different cultural contexts.